Are Indonesia SMEs Interested in Switching Funding to Sharia P2P Lending? A Push-Pull-Mooring Framework - Tantriana, Deasy; Pratikto, Heri; Handayati, Puji; Wardoyo, Cipto (Journal of Ecohumanism, 2024)
This study examines the switching behavior to peer-to-peer (P2P) lending platforms to determine the factors that encourage SMEs to use Sharia P2P lending platforms to obtain loans. This study focuses on the factors that contribute to the intention to switch SME funding from conventional banking to Sharia P2P lending in Indonesia. Using questionnaires and purposive sampling, we collected data from a total of 367 SMEs in Indonesia that use Sharia P2P lending and then applied PLS-SEM for data analysis. The results showed that the pull effect significantly influenced the intention of SME owners to switch to Sharia P2P lending and was negatively moderated by switching costs. In contrast, the push effect did not significantly influence the intention to switch to Sharia P2P lending. In addition, switching costs directly influenced the intention of SME owners to switch from conventional banking funding to Sharia P2P lending.